Design PID-Like Fuzzy Controller With Minimum Rule Base and Mathematical Proposed On-line Tunable Gain: Applied to Robot Manipulator. - Sulaiman, Nasri; Piltan, Farzin; Zargari, Arash; Keshavarz, Mohammad; Badri, Ali (2011)
In this study, an on-line tunable gain model free PID-like fuzzy controller (GTFLC) is designed forthree degrees of freedom (3DOF) robot manipulator to rich the best performance. Fuzzy logiccontroller is studied because of its model free and high performance. Today, robot manipulatorsare used in unknown and unstructured environment and caused to provide sophisticated systems,therefore strong mathematical tools are used in new control methodologies to design adaptivenonlinear robust controller with acceptable performance (e.g., minimum error, good trajectory,disturbance rejection). The strategies of control robot manipulator are classified into two maingroups: classical and non-classical methods, however non linear classical theories have beenapplied successfully in many applications, but they also have some limitation. One of the mostimportant nonlinear non classical robust controller that can used in uncertainty nonlinear systems,are fuzzy logic controller. This paper is focuses on applied mathematical tunable gain method inrobust non classical method to reduce the fuzzy logic controller limitations. Therefore on-linetunable PID like fuzzy logic controller will be presented in this paper.